2001
DOI: 10.1093/nar/29.12.2535
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus internal ribosome entry site RNA contains a tertiary structural element in a functional domain of stem-loop II

Abstract: The internal ribosome entry site (IRES) of hepatitis C virus (HCV) RNA contains >300 bases of highly conserved 5'-terminal sequence, most of it in the uncapped 5'-untranslated region (5'-UTR) upstream from the single AUG initiator triplet at which translation of the HCV polyprotein begins. Although progress has been made in defining singularities like the RNA pseudoknot near this AUG, the sequence and structural features of the HCV IRES which stimulate accurate and efficient initiation of protein synthesis are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 23 publications
6
46
0
1
Order By: Relevance
“…Images shown in Figure 2 have been reproducibly observed in two independent experiments obtained by means of different labelled RNA transcript preparations. These results are in agreement with previous ones using RNase H and DNA (43)(44)(45), and demonstrate the suitability of the proposed method to distinguish highly structured RNA from less structured ones, in the HCV genome. Macroarrays were printed manually and compared by visual inspection and therefore not used for fine quantitation purposes but they suggested that the approach was valid and we could go to the next step using microarrays.…”
Section: A First Approach On Macroarrayssupporting
confidence: 91%
See 3 more Smart Citations
“…Images shown in Figure 2 have been reproducibly observed in two independent experiments obtained by means of different labelled RNA transcript preparations. These results are in agreement with previous ones using RNase H and DNA (43)(44)(45), and demonstrate the suitability of the proposed method to distinguish highly structured RNA from less structured ones, in the HCV genome. Macroarrays were printed manually and compared by visual inspection and therefore not used for fine quantitation purposes but they suggested that the approach was valid and we could go to the next step using microarrays.…”
Section: A First Approach On Macroarrayssupporting
confidence: 91%
“…These oligonucleotides were complementary to specific viral regions in which the genomic RNA adopts different degrees of structure, as previously measured by means of RNase H accessibility studies (44,45) (Figure 1A). …”
Section: Oligonucleotide Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial secondary structure had been predicted using both enzymatic probing results as constraints in an early version of the MFOLD program (Zuker and Stiegler 1981) along with comparative computer-predicted models with the UTRs of BVDV and CSFV (Brown et al 1992). There have been numerous studies adding to the refinement of the IRES structure (Lemon and Honda 1997;Lyons et al 2001;Odreman-Macchioli et al 2001), arriving at two similar models (Honda et al 1999;Zhao and Wimmer 2001;Lytle et al 2002) with some differences in domain II. Smaller stem-loop motifs of the HCV IRES structure have had their tertiary structure determined using both X-ray crystallography (Kieft et al 2002) and NMR (Klinck et al 2000;Lukavsky et al 2000;Collier et al 2002).…”
Section: Viral Ires Structuresmentioning
confidence: 99%